Hubungan Kadar Trigliserida dengan Tekanan Sistolik dan Diastolik - Thoha, Thoha; Kusniawati, Kusniawati; Subiakto, Toto; Akbar, Roby Rahmadi (Faletehan Health Journal, 2024)
Hypertension is a condition when the pressure in the blood vessels increases beyond normal limits. High triglyceride levels can be associated with increased blood pressure which can cause heart problems. This study aimed to determine the relationship between triglycerides and systolic and diastolic pressure. This was analytical correlative research with a cross-sectional approach. A total of 38 respondents who were adult individuals aged 30-50 years were involved in the study using an accidental sampling technique. The correlation between variables was tested using Spearman’s rank. The results showed that the mean of triglyceride level was 203.79 (SD=40.036), systolic pressure 149.05 (SD-24.052), and diastolic pressure 89.00 (SD=11.128). The results of the Spearman correlation test showed there was no significant correlation between triglyceride levels, systolic pressure (p value=0.472) and diastolic pressure (p value=0.710). The triglyceride levels of hypertensive patients with increased systolic and diastolic pressures above normal pressure were often found high. However, high triglyceride conditions were not necessarily accompanied by an increase in systolic and diastolic pressure.